SOCIOLOGY IN BRAZILIAN HIGH SCHOOL EDUCATION: CURRICULAR DISPUTES, NEOLIBERALISM, AND CRITICAL THINKING - Krauss, Alessandra; Cristiano Voznei, Leanderson (Revista Gênero e Interdisciplinaridade, 2026)
This article aims to understand the historical process of the inclusion of Sociology in Brazilian High School education, reflecting on the political and curricular disputes that permeate the discipline and its contributions to the critical and emancipatory formation of students in the context of contemporary neoliberal educational reforms. The research is guided by the following problem: how does the historical process of the inclusion of Sociology in Brazilian High School reveal the political and curricular disputes present in contemporary educational reforms, especially in the face of the advance of neoliberal logic in education? The investigation is based on a qualitative approach, with bibliographic and documentary research, grounded in the perspective of Critical Hermeneutics. The study historically comprehends the trajectory of Sociology within the Brazilian school curriculum, from the first proposals for its inclusion at the end of the nineteenth century, through the educational reforms of the twentieth century, the removal of the discipline during authoritarian periods, its mandatory status in 2008, and the impacts of the 2017 High School Reform and the National Common Curricular Base (BNCC). The theoretical framework is supported by authors such as Giddens (2012), Tomazi (2000), Moraes (2011), Rêses (2004), Freitas and França (2016), Sell (2015), Gadamer (1997; 2007), and Freire (1996; 2002; 2021), among other scholars in the fields of Sociology and Education. The reflections developed demonstrate that Sociology plays a fundamental role in the critical formation of students, contributing to the understanding of social inequalities, power relations, and contradictions present in contemporary society. However, the study also reveals that current educational policies, influenced by neoliberal rationality, have weakened the Humanities within the school curriculum, reducing the space of Sociology in High School education through curricular flexibilization and the weakening of critical educational formation. It is concluded that Sociology remains an important instrument for critical, civic, and emancipatory formation, being essential for strengthening democracy, social awareness, and the development of subjects capable of critically understanding and transforming the social reality in which they live.